(untitled) (Intent Research Scientific Journal, 2023)
The article covers the model for automatic compensation of reactive component of consumed current of asynchronous motors operating at powers lower than the nominal values. Automated control system for individual compensation of reactive component of power consumption have been designed, which is connected directly to asynchronous electric motors of machine tools